RECUPERAÇÃO SÓCIO-AMBIENTAL DE ÁREA DE ANTIGA PEDREIRA - ALANA ECKHARDT , JÚLIA; BASSO , LAURÍ; MARGARETE BACCIN BRIZOLLA , MARIA; NEY KUHN , IVO; LIBARDONI VIEIRA , EILAMARIA; LUIS ALLEBRANDT , SERGIO (Salão do Conhecimento, 2020)
Projeto de Extensão Gestão Social e Cidadania